2023
DOI: 10.2478/fhort-2023-0017
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of different planting times on fruit quality and some bioactive contents of different strawberry cultivars

Abstract: Strawberry fruit quality traits can be affected by genotype-environment interactions, which determine the consumer acceptance of fruits. This factorial experiment was based on completely randomised blocks (RCBD) with two planting dates (5 and 20 April) and cultivars (‘Albion’, ‘San Andreas’ and ‘Portola’) of strawberry with three replications, and some of pomological and qualitative factors of berry were investigated at harvest. The results showed no significant difference on fruit width, length, weight and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The content of the mentioned components is largely a genetic trait, depending on the species and cultivar [50]. In addition to genetic factors [61], bioactive compound content is influenced by a number of external factors, such as fruit maturity, exposure of fruit to sunlight, length, and type of storage or cultivation location [62][63][64]. The cultivars evaluated in this experiment also differed in their content of bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The content of the mentioned components is largely a genetic trait, depending on the species and cultivar [50]. In addition to genetic factors [61], bioactive compound content is influenced by a number of external factors, such as fruit maturity, exposure of fruit to sunlight, length, and type of storage or cultivation location [62][63][64]. The cultivars evaluated in this experiment also differed in their content of bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly regarded for the health, quality, and taste benefits of fruits [6,7]. Many authors have shown that both the leaves and fruits of strawberries possess a rich chemical profile, including readily absorbable sugars, dietary fibers, vitamins (especially vitamin C), and a range of bioactive compounds with antioxidant properties [8][9][10][11]. A prospective option for improving plant growth and drought tolerance is the application of plant growth-promoting rhizobacteria (PGPR) as inocules.…”
Section: Of 31mentioning
confidence: 99%
“…Due to their common occurrence in plants, anthocyanins are present in the human diet. Quantitative and qualitative differences in the anthocyanin composition of fruit imply that these characteristics depend on plant species [ 12 ], cultivar [ 13 ], growth conditions [ 14 ], ripeness, storage [ 15 ], and processing methods [ 16 ]. The main sources of anthocyanins in a temperate climate zone are grapes, chokeberry, blackcurrant, and elderberry.…”
Section: Introductionmentioning
confidence: 99%